Application of a class of inorganic materials in the preparation of color-changing polymer materials
By adding inorganic materials containing tungsten and/or molybdenum to the polymer, color marking is realized on light-colored substrates by using laser marking technology, solving the problem that laser color marking is difficult to realize on light-colored substrates in the prior art. It achieves efficient and environmentally friendly color marking effect, suitable for industrial applications.
Patent Information
- Application Number
- CN202211708363.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-28
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-12-28
AI Technical Summary
The prior art is difficult to implement laser color marking on light-colored or white polymer substrates, and the existing color marking methods are complex in process and high in cost, which limits their promotion in industrial applications.
Using inorganic materials containing tungsten and/or molybdenum as additives, combining polymers with polymers to prepare color-changing polymer materials, and forming color marks on the polymers through laser marking technology, and using photothermal and photochemical effects to make inorganic materials occur. Color changes.
It realizes high contrast and clear color markings on light-colored substrates, expands the application range of laser color markings, and has a simple process, safe and environmentally friendly, suitable for industrial production.
Smart Images

Figure CN115895091B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer laser processing, and specifically relates to the application of a type of inorganic material in the preparation of a color-changeable polymer material, and also relates to a color-changeable polymer material prepared based on the type of inorganic material and a preparation method thereof. Background Art
[0002] Laser marking is a method of using high-energy-density lasers to irradiate the surface of materials to cause chemical reactions such as carbonization, discoloration, and foaming, thereby obtaining a permanent mark with a different color from the substrate. At present, laser marking is mainly used for permanent marking and product anti-counterfeiting. Compared with traditional marking methods such as ink printing, screen printing, embossing, and hot stamping, laser marking is gradually becoming a popular marking method because of its advantages of high processing accuracy, high marking efficiency, simple operation, non-contact, low cost, and cleanliness.
[0003] The current laser marking method mainly generates white or light-colored marks on the surface of black (or dark gray, gray) polymer materials, or marks black patterns and texts on polymer substrates with light backgrounds. For example: Chinese patent application with publication number CN105504517A discloses the use of graphene as an additive in the preparation of laser-markable polymer materials, which can achieve black marking on the polymer surface; Chinese patent with announcement number CN104804360B discloses an impact-resistant ABS resin composition with the function of printing white markings on a black matrix using laser. However, it is difficult to perform laser color marking on the surface of polymers. Polymer laser color marking is still a hot spot and difficulty in industry and academia.
[0004] A Chinese patent application with publication number CN106566068A discloses a polymer composition that can be laser-marked in color. The patent uses a polymer, a laser marking powder and a temperature-sensitive substance. The heat generated during the laser marking process can cause the temperature-sensitive substance to undergo thermal decomposition, oxidation and other reactions at a certain temperature to produce a new color, thereby forming a similar color mark on the polymer. The temperature-sensitive substance used in the invention is at least one of the phthalocyanine pigments, and a specific laser marking powder needs to be added to the composition. The process cost is high and it is not suitable for large-scale industrial applications. Moreover, the laser marking powder and phthalocyanine pigments added in the invention are black or dark substances, so the base color of the polymer composition that can be laser-marked in color is black or dark.
[0005] The Chinese patent application with publication number CN109486128A discloses a plastic paper that can be laser-marked in color, and its raw materials include plastic material, sodium allyl sulfonate, initiator, black pigment, color pigment, antioxidant, flame retardant, lubricant, and filler that can be added or not. The composition in the invention needs to add black pigment, so it can only mark color in black substrate, which greatly limits its application in the field of laser color marking. In addition, the composition has many ingredients, the process is too complicated, the implementation is difficult, the resource consumption is large, and it is difficult to put into large-scale production.
[0006] At present, polymer laser color change mainly uses laser to achieve color change on black or dark base polymers, and the color of the color change depends on the color of the pigment added to the polymer. However, there is no patent literature reporting the use of laser to achieve color change on light or white polymer bases. Therefore, it is urgent to find a new laser color change polymer material that can simply and conveniently use laser to perform color marking on light or white polymer materials. Summary of the invention
[0007] The purpose of the present invention is to provide an application of a type of inorganic material in the preparation of a color-changeable polymer material, and at the same time provide a color-changeable polymer material prepared based on the type of inorganic material and a preparation method thereof.
[0008] The invention provides application of an inorganic material in preparing a color-changeable polymer material, wherein the inorganic material is an inorganic compound containing tungsten and / or molybdenum.
[0009] Further, the tungsten-containing inorganic compound is selected from at least one of tungsten-containing acid, tungsten oxide, and tungsten-containing salt; the molybdenum-containing inorganic compound is selected from at least one of molybdenum-containing acid, molybdenum oxide, molybdenum hydroxide, and molybdenum-containing salt;
[0010] Preferably,
[0011] The tungsten oxide is selected from any one or more of molybdenum-doped tungsten oxide, tantalum-doped tungsten oxide, WO3, sodium-doped tungsten oxide, potassium-doped tungsten oxide, titanium-doped tungsten oxide, and indium-doped tungsten oxide;
[0012] And / or, the tungsten-containing acid is selected from any one or more of tungstic acid, phosphotungstic acid, and silicotungstic acid;
[0013] And / or, the tungsten-containing salt is selected from any one or more of tungsten phosphate, tungsten sulfate, tungsten nitrate, tungsten silicate, tungsten carbonate, tungsten aluminate, tungsten bismuthate, ammonium tungstate, ammonium metatungstate, ammonium paratungstate, sodium tungstate, potassium tungstate, calcium tungstate, bismuth tungstate, zinc tungstate, lithium tungstate, molybdenum tungstate, lead tungstate, sodium phosphotungstate, and niobium tungstate;
[0014] And / or, the molybdenum oxide is selected from any one or more of molybdenum aluminum oxide, molybdenum copper oxide, MoO3, molybdenum zinc oxide, and molybdenum titanium oxide;
[0015] And / or, the molybdenum hydroxide is molybdenum hydroxide;
[0016] And / or, the molybdenum-containing acid is selected from any one or more of molybdic acid, phosphomolybdic acid, and silicomolybdic acid;
[0017] And / or, the molybdenum-containing salt is selected from any one or more of molybdenum phosphate, molybdenum sulfate, molybdenum nitrate, molybdenum silicate, molybdenum carbonate, molybdenum aluminate, molybdenum bismuthate, ammonium paramolybdate, ammonium metamolybdate, ammonium molybdate, sodium molybdate, potassium molybdate, cesium molybdate, calcium molybdate, bismuth molybdate, nickel molybdate, zinc molybdate, lithium molybdate, sodium phosphomolybdate, sodium silicomolybdate, and niobium molybdate;
[0018] More preferably,
[0019] The tungsten oxide is selected from molybdenum-doped tungsten oxide, sodium-doped tungsten oxide, WO3 or titanium-doped tungsten oxide;
[0020] and / or, the tungsten-containing acid is selected from tungstic acid;
[0021] and / or, the tungsten-containing salt is selected from ammonium tungstate, ammonium metatungstate, ammonium paratungstate, sodium tungstate, zinc tungstate or bismuth tungstate;
[0022] And / or, the molybdenum oxide is selected from molybdenum aluminum oxide, molybdenum zinc oxide, MoO3 or molybdenum titanium oxide;
[0023] and / or, the molybdenum-containing acid is selected from molybdic acid, phosphomolybdic acid or silicomolybdic acid;
[0024] And / or, the molybdenum-containing salt is selected from ammonium molybdate, ammonium metamolybdate or sodium molybdate.
[0025] Furthermore, the average particle size of the inorganic material is less than or equal to 100 μm; preferably, the average particle size of the inorganic material is 0.005 μm to 50 μm; more preferably, the average particle size of the inorganic material is 0.01 μm to 20 μm.
[0026] The present invention also provides a polymer color-changing composition based on inorganic materials, which is composed of the following components in weight percentage: 0.1% to 45% of inorganic materials and 55% to 99.9% of polymers;
[0027] The inorganic material is an inorganic compound containing tungsten and / or molybdenum;
[0028] Preferably, it is composed of the following components in weight percentage: 0.5% to 40% inorganic material, 60% to 99.5% polymer;
[0029] More preferably, it is composed of the following components in weight percentage: 1% to 30% inorganic material, 70% to 99% polymer;
[0030] More preferably, it is composed of the following components in weight percentage: 2% to 30% inorganic material and 70% to 98% polymer.
[0031] Further,
[0032] The tungsten-containing inorganic compound is selected from at least one of tungsten-containing acid, tungsten oxide, and tungsten-containing salt; the molybdenum-containing inorganic compound is selected from at least one of molybdenum-containing acid, molybdenum oxide, molybdenum hydroxide, and molybdenum-containing salt;
[0033] Preferably,
[0034] The tungsten oxide is selected from any one or more of molybdenum-doped tungsten oxide, tantalum-doped tungsten oxide, WO3, sodium-doped tungsten oxide, potassium-doped tungsten oxide, titanium-doped tungsten oxide, and indium-doped tungsten oxide;
[0035] And / or, the tungsten-containing acid is selected from any one or more of tungstic acid, phosphotungstic acid, and silicotungstic acid;
[0036] And / or, the tungsten-containing salt is selected from any one or more of tungsten phosphate, tungsten sulfate, tungsten nitrate, tungsten silicate, tungsten carbonate, tungsten aluminate, tungsten bismuthate, ammonium tungstate, ammonium metatungstate, ammonium paratungstate, sodium tungstate, potassium tungstate, calcium tungstate, bismuth tungstate, zinc tungstate, lithium tungstate, molybdenum tungstate, lead tungstate, sodium phosphotungstate, and niobium tungstate;
[0037] And / or, the molybdenum oxide is selected from any one or more of molybdenum aluminum oxide, molybdenum copper oxide, MoO3, molybdenum zinc oxide, and molybdenum titanium oxide;
[0038] And / or, the molybdenum hydroxide is molybdenum hydroxide;
[0039] And / or, the molybdenum-containing acid is selected from any one or more of molybdic acid, phosphomolybdic acid, and silicomolybdic acid;
[0040] And / or, the molybdenum-containing salt is selected from any one or more of molybdenum phosphate, molybdenum sulfate, molybdenum nitrate, molybdenum silicate, molybdenum carbonate, molybdenum aluminate, molybdenum bismuthate, ammonium paramolybdate, ammonium metamolybdate, ammonium molybdate, sodium molybdate, potassium molybdate, cesium molybdate, calcium molybdate, bismuth molybdate, nickel molybdate, zinc molybdate, lithium molybdate, sodium phosphomolybdate, sodium silicomolybdate, and niobium molybdate;
[0041] More preferably,
[0042] The tungsten oxide is selected from molybdenum-doped tungsten oxide, sodium-doped tungsten oxide, WO3 or titanium-doped tungsten oxide;
[0043] and / or, the tungsten-containing acid is selected from tungstic acid;
[0044] and / or, the tungsten-containing salt is selected from ammonium tungstate, ammonium metatungstate, ammonium paratungstate, sodium tungstate, zinc tungstate or bismuth tungstate;
[0045] And / or, the molybdenum oxide is selected from molybdenum aluminum oxide, molybdenum zinc oxide, MoO3 or molybdenum titanium oxide;
[0046] and / or, the molybdenum-containing acid is selected from molybdic acid, phosphomolybdic acid or silicomolybdic acid;
[0047] And / or, the molybdenum-containing salt is selected from ammonium molybdate, ammonium metamolybdate or sodium molybdate.
[0048] Furthermore, the average particle size of the inorganic material is less than or equal to 100 μm; preferably, the average particle size of the inorganic material is 0.005 μm to 50 μm; more preferably, the average particle size of the inorganic material is 0.01 μm to 20 μm.
[0049] Further, the polymer is selected from any one or more of polyethylene, polypropylene, nylon, polycarbonate, polymethyl methacrylate, polyethyl methacrylate, polybutyl methacrylate, polyoxymethylene, polyethylene terephthalate, polybutylene terephthalate, ethylene-octene copolymer, ethylene-butene copolymer, ethylene-acrylic acid copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene copolymer, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polyurethane elastomer, polyester elastomer, styrene thermoplastic elastomer, styrene-butadiene copolymer, styrene-methacrylate copolymer, polyisobutylene, ethylene-vinyl acetate copolymer, polysulfone, polyimide, cellulose acetate, unsaturated polyester, silicone resin, epoxy resin, phenolic resin, melamine resin, natural rubber, butadiene rubber, styrene-butadiene rubber, silicone rubber, fluororubber, nitrile rubber, butyl rubber, and EPDM rubber;
[0050] Preferably, the polymer is selected from polymethyl methacrylate, polyethylene, polypropylene, polystyrene, acrylonitrile-butadiene-styrene copolymer, nylon 66, polycarbonate, polyoxymethylene, polyurethane elastomer, polyester elastomer, polyethylene terephthalate, polybutylene terephthalate.
[0051] The present invention also provides a method for preparing the aforementioned polymer color-changing composition, which comprises the following steps:
[0052] a. Take an inorganic material and a polymer, mix them evenly, and obtain a mixture;
[0053] b. Melt and blend the mixture obtained in step a, and granulate to obtain the product.
[0054] The present invention also provides the use of the aforementioned polymer color-changing composition in the preparation of laser color marking.
[0055] The present invention also provides a laser color mark, which is a color pattern or text produced by irradiating the aforementioned polymer color-changing composition with laser;
[0056] Preferably, the laser is emitted by a CO2 laser (10.6 μm), a Nd:YAG laser (1064, 532, 355 and 266 nm), a Nd:YVO4 laser (1064, 532, 355 and 266 nm), an excimer laser (F2 (157 nm), ArF (193 nm), KrCl (222 nm), KrF (248 nm), XeCl (308 nm) and XeF (351 nm)), a fiber laser, a diode array laser or a diode laser; the wavelength of the laser is 157 nm to 10.6 μm;
[0057] More preferably, the laser is emitted by a pulsed Nd:YAG laser or a pulsed fiber laser; the wavelength of the laser is 1064nm, 532nm or 355nm;
[0058] Further preferably, the laser energy is 0.5-8 W; and / or, the laser frequency is 10-100 kHz; and / or, the laser marking speed is 400-4000 mm / s.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] The present invention provides a color-changeable polymer material prepared based on inorganic materials. The present invention prepares a color-changeable polymer material by adding a specific inorganic material as an additive into a polymer. Under the action of a laser, the polymer material has an excellent color-change effect. Laser marking is performed on the polymer material to form various color marks on the polymer material, and the obtained color marks are clear, flat and have a high contrast. At the same time, the polymer material has a light color, and color marking can be achieved on a light-colored substrate, which expands the application range of laser color marking. In addition, the preparation method of the color-changeable polymer material of the present invention is simple, easy to operate, safe, environmentally friendly, and very suitable for industrial applications. The present invention broadens the application field of polymer laser color change and has good application prospects.
[0061] After the inorganic material provided by the present invention is introduced into the polymer as an additive, the photothermal effect and photochemical effect generated during the laser marking process are used to change the inorganic material, thereby generating a new color. This color change is irreversible, so a stable permanent color change can be formed on the polymer material.
[0062] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0063] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is a photo of the polymer laser color change effect after adding inorganic material additives in Example 17. DETAILED DESCRIPTION
[0065] The raw materials and equipment used in the specific embodiments of the present invention are all known products and are obtained by purchasing commercially available products.
[0066] (1) The equipment information used in the present invention is as follows:
[0067] Twin-screw extruder, screw diameter 35 mm, screw length-diameter ratio 36:1, produced by Nanjing Jieente Electromechanical Co., Ltd.;
[0068] Injection molding machine, model MA600, produced by Haitian Machinery Co., Ltd.;
[0069] Laser marking machine, model MUV-ER, pulse fiber laser marking machine, laser maximum power 10W, laser wavelength 355nm.
[0070] (2) The specific information of the polymer used to prepare the standard sample of the present invention is as follows:
[0071] Polyethylene (PE): Maoming Petrochemical, TR144;
[0072] Polypropylene (PP): Sinopec Lanzhou Branch, T30S;
[0073] Polymethyl methacrylate (PMMA): Evonik Degussa, Germany, 8803;
[0074] Polystyrene: Duzishan Petrochemical, GPPS-500;
[0075] Acrylonitrile butadiene styrene (ABS): Chimei, Taiwan, China, PA757;
[0076] Polyoxymethylene (POM): Shenhua, MC90;
[0077] Nylon 66: Lanxess, Germany, A30S;
[0078] Polyethylene terephthalate: Yuanfang Industrial, CB-602;
[0079] Polybutylene terephthalate: BASF, Germany, PBTB4500;
[0080] Polycarbonate: General Electric Company, PC121R;
[0081] Polyurethane: Bayer, Germany, 9385;
[0082] Polyester elastomer: Korean Kelong, KP3355.
[0083] Example 1
[0084] First, 95 g of polyethylene resin and 5 g of ammonium tungstate powder (average particle size of 3 μm), an inorganic material additive, are fully mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 160°C to obtain a polymer material that can change color by laser.
[0085] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 160°C.
[0086] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 2 W, the laser frequency was 50 kHz, and the color change effect was shown in Table 1.
[0087] Example 2
[0088] A polymer material capable of laser color change was prepared by referring to the method of Example 1, with the only difference being that the base polymer and the inorganic material additive used were: 85 g of polyethylene resin and 15 g of ammonium tungstate powder, an inorganic material additive. Other conditions were the same as in Example 1. The color change effect is shown in Table 1.
[0089] Example 3
[0090] First, 97 g of polypropylene resin and 3 g of ammonium metatungstate powder (average particle size of 2 μm), an inorganic material additive, are fully mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 190°C to obtain a polymer material that can change color by laser.
[0091] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 190°C.
[0092] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3.5 W, the laser frequency was 90 kHz, and the color change effect was shown in Table 1.
[0093] Example 4
[0094] The polymer material capable of laser color change was prepared by referring to the method of Example 3, the only difference being that the base polymer and the inorganic material additive used were: 90 g of polypropylene resin and 10 g of ammonium metatungstate powder, the other conditions were the same as those of Example 3, and the color change effect is shown in Table 1.
[0095] Example 5
[0096] First, 95 g of polystyrene resin and 5 g of ammonium paratungstate powder (average particle size of 5 μm), an inorganic material additive, are fully mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 210°C to obtain a polymer material that can change color by laser.
[0097] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 210°C.
[0098] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 4 W, the laser frequency was 80 kHz, and the color change effect was shown in Table 1.
[0099] Example 6
[0100] The polymer material capable of laser color change was prepared by referring to the method of Example 5, the only difference being that the base polymer and the inorganic material additive used were: 90 g of polystyrene resin and 10 g of ammonium paratungstate powder, the other conditions were the same as those of Example 5, and the color change effect is shown in Table 1.
[0101] Example 7
[0102] First, 95 g of ABS resin and 5 g of sodium tungstate powder (average particle size of 20 μm), an inorganic material additive, were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 210°C to obtain a polymer material that can change color with laser light.
[0103] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 210°C.
[0104] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 70 kHz, and the color change effect was shown in Table 1.
[0105] Example 8
[0106] A polymer material capable of laser color change was prepared by referring to the method of Example 7, the only difference being that the base polymer and the inorganic material additive used were: 80 g of ABS resin and 20 g of sodium tungstate powder, an inorganic material additive. Other conditions were the same as those of Example 7. The color change effect is shown in Table 1.
[0107] Example 9
[0108] First, 99 g of polymethyl methacrylate resin and 1 g of inorganic material additive WO3 powder (average particle size of 1 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 240°C to obtain a polymer material that can change color by laser.
[0109] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 240°C.
[0110] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 80 kHz, and the color change effect was shown in Table 1.
[0111] Example 10
[0112] The polymer material capable of laser color change was prepared by referring to the method of Example 9, the only difference being that the base polymer and the inorganic material additive used were: 95 g of polymethyl methacrylate resin and 5 g of WO3 powder, the other conditions were the same as those of Example 9, and the color change effect is shown in Table 1.
[0113] Embodiment 11
[0114] The polymer material capable of laser color change was prepared by referring to the method of Example 9, the only difference being that the base polymer and the inorganic material additive used were: 90 g of polymethyl methacrylate resin and 10 g of WO3 powder, the other conditions were the same as those of Example 9, and the color change effect is shown in Table 1.
[0115] Example 12
[0116] First, 90 g of nylon 66 resin and 10 g of molybdenum-doped tungsten oxide powder (average particle size of 0.5 μm) as an inorganic material additive are fully mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 230°C to obtain a polymer material that can change color by laser.
[0117] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 240°C.
[0118] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 70 kHz, and the color change effect was shown in Table 1.
[0119] Embodiment 13
[0120] A polymer material capable of laser color change was prepared by referring to the method of Example 12, with the only difference being that the base polymer and the inorganic material additive used were: 80 g of nylon 66 resin and 20 g of molybdenum-doped tungsten oxide powder, an inorganic material additive. Other conditions were the same as in Example 12. The color change effect is shown in Table 1.
[0121] Embodiment 14
[0122] First, 90 g of polycarbonate resin and 10 g of sodium-doped tungsten oxide powder (average particle size of 0.2 μm) as an inorganic material additive are fully mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 260°C to obtain a polymer material that can change color by laser.
[0123] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 270°C.
[0124] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 2 W, the laser frequency was 30 kHz, and the color change effect was shown in Table 1.
[0125] Embodiment 15
[0126] A polymer material capable of laser color change was prepared by referring to the method of Example 14, with the only difference being that the base polymer and the inorganic material additive used were: 70 g of polycarbonate resin and 30 g of sodium-doped tungsten oxide powder, an inorganic material additive. Other conditions were the same as those of Example 14. The color change effect is shown in Table 1.
[0127] Example 16
[0128] First, 90 g of polyoxymethylene resin and 10 g of titanium-doped tungsten oxide powder (average particle size of 0.8 μm) as an inorganic material additive are fully mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 200°C to obtain a polymer material that can change color by laser.
[0129] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 205°C.
[0130] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 50 kHz, and the color change effect was shown in Table 1.
[0131] Embodiment 17
[0132] A polymer material capable of laser color change was prepared by referring to the method of Example 16, with the only difference being that the base polymer and the inorganic material additive used were: 80 g of polyoxymethylene resin and 20 g of titanium-doped tungsten oxide powder, an inorganic material additive. Other conditions were the same as those of Example 16. The color change effect is shown in Table 1.
[0133] Embodiment 18
[0134] First, 95 g of polyurethane resin and 5 g of inorganic material additive zinc tungstate powder (average particle size of 4 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 190°C to obtain a polymer material that can change color by laser.
[0135] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 190°C.
[0136] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 4.5 W, the laser frequency was 90 kHz, and the color change effect was shown in Table 1.
[0137] Embodiment 19
[0138] A polymer material capable of laser color change was prepared by referring to the method of Example 18, with the only difference being that the base polymer and the inorganic material additive used were: 85 g of polyurethane resin and 15 g of zinc tungstate powder, an inorganic material additive. Other conditions were the same as those of Example 18. The color change effect is shown in Table 1.
[0139] Embodiment 20
[0140] First, 90 g of polyester elastomer resin and 10 g of tungstic acid powder (average particle size of 12 μm) as an inorganic material additive are thoroughly mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 190°C to obtain a polymer material that can change color by laser.
[0141] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 190°C.
[0142] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 4 W, the laser frequency was 55 kHz, and the color change effect was shown in Table 1.
[0143] Embodiment 21
[0144] A polymer material capable of laser color change was prepared by referring to the method of Example 20, with the only difference being that the base polymer and the inorganic material additive used were: 80 g of polyester elastomer resin and 20 g of tungstic acid powder, an inorganic material additive. Other conditions were the same as those of Example 20. The color change effect is shown in Table 1.
[0145] Embodiment 22
[0146] First, 90 g of polyethylene terephthalate resin and 10 g of ammonium tungstate powder (average particle size of 15 μm), an inorganic material additive, were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 240°C to obtain a polymer material that can change color by laser.
[0147] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 250°C.
[0148] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 2.5 W, the laser frequency was 20 kHz, and the color change effect was shown in Table 1.
[0149] Embodiment 23
[0150] A polymer material capable of laser color change was prepared by referring to the method of Example 22, with the only difference being that the base polymer and the inorganic material additive used were: 70 g of polyethylene terephthalate resin and 30 g of ammonium tungstate powder, an inorganic material additive. Other conditions were the same as in Example 22. The color change effect is shown in Table 1.
[0151] Embodiment 24
[0152] First, 85 g of polybutylene terephthalate resin and 15 g of bismuth tungstate powder (average particle size of 10 μm), an inorganic material additive, were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 265°C to obtain a polymer material that can change color by laser.
[0153] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 270°C.
[0154] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 4 W, the laser frequency was 100 kHz, and the color change effect was shown in Table 1.
[0155] Embodiment 25
[0156] A polymer material capable of laser color change was prepared by referring to the method of Example 24, with the only difference being that the base polymer and the inorganic material additive used were: 70 g of polybutylene terephthalate resin and 30 g of bismuth tungstate powder, an inorganic material additive. Other conditions were the same as those of Example 24. The color change effect is shown in Table 1.
[0157] Embodiment 26
[0158] First, 98 g of polyurethane resin and 2 g of MoO3 powder (average particle size of 1.5 μm), an inorganic material additive, were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 190°C to obtain a polymer material that can change color by laser.
[0159] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 190°C.
[0160] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 60 kHz, and the color change effect was shown in Table 1.
[0161] Embodiment 27
[0162] A polymer material capable of laser color change was prepared by referring to the method of Example 26, with the only difference being that the base polymer and the inorganic material additive used were: 90 g of polyurethane resin and 10 g of MoO3 powder, an inorganic material additive. Other conditions were the same as those of Example 26. The color change effect is shown in Table 1.
[0163] Embodiment 28
[0164] First, 95 g of polypropylene resin and 5 g of inorganic material additive molybdenum aluminum oxide powder (average particle size of 1 μm) are fully mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 190°C to obtain a polymer material that can change color by laser.
[0165] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 190°C.
[0166] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 5 W, the laser frequency was 90 kHz, and the color change effect was shown in Table 1.
[0167] Embodiment 29
[0168] A polymer material capable of laser color change was prepared by referring to the method of Example 28, with the only difference being that the base polymer and the inorganic material additive used were: 80 g of polypropylene resin and 20 g of the inorganic material additive molybdenum aluminum oxide powder. Other conditions were the same as in Example 28. The color change effect is shown in Table 1.
[0169] Embodiment 30
[0170] First, 97 g of polyethylene resin and 3 g of inorganic material additive molybdenum zinc oxide powder (average particle size of 0.5 μm) are fully mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 160°C to obtain a polymer material that can change color by laser.
[0171] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 160°C.
[0172] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 4 W, the laser frequency was 65 kHz, and the color change effect was shown in Table 1.
[0173] Embodiment 31
[0174] A polymer material capable of laser color change was prepared by referring to the method of Example 30, with the only difference being that the base polymer and the inorganic material additive used were: 85 g of polyethylene resin and 15 g of inorganic material additive molybdenum zinc oxide powder. Other conditions were the same as in Example 30. The color change effect is shown in Table 1.
[0175] Embodiment 32
[0176] First, 95 g of nylon 66 resin and 5 g of inorganic material additive molybdenum titanium oxide powder (average particle size of 0.1 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 230°C to obtain a polymer material that can change color by laser.
[0177] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 240°C.
[0178] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3.5 W, the laser frequency was 40 kHz, and the color change effect was shown in Table 1.
[0179] Embodiment 33
[0180] A polymer material capable of laser color change was prepared by referring to the method of Example 32, with the only difference being that the base polymer and the inorganic material additive used were: 90 g of nylon 66 resin and 10 g of the inorganic material additive molybdenum titanium oxide powder. Other conditions were the same as in Example 32. The color change effect is shown in Table 1.
[0181] Embodiment 34
[0182] First, 90 g of polymethyl methacrylate resin and 10 g of inorganic material additive molybdenum hydroxide powder (average particle size of 8 μm) are fully mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 240°C to obtain a polymer material that can change color by laser.
[0183] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 240°C.
[0184] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 25 kHz, and the color change effect was shown in Table 1.
[0185] Embodiment 35
[0186] A polymer material capable of laser color change was prepared by referring to the method of Example 34, with the only difference being that the base polymer and the inorganic material additive used were: 80 g of polymethyl methacrylate resin and 20 g of inorganic material additive molybdenum hydroxide powder. Other conditions were the same as in Example 34. The color change effect is shown in Table 1.
[0187] Embodiment 36
[0188] First, 98 g of polyformaldehyde resin and 2 g of molybdic acid powder (average particle size of 5 μm), an inorganic material additive, are fully mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 200°C to obtain a polymer material that can change color by laser.
[0189] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 205°C.
[0190] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3.5 W, the laser frequency was 70 kHz, and the color change effect was shown in Table 1.
[0191] Embodiment 37
[0192] A polymer material capable of laser color change was prepared by referring to the method of Example 36, with the only difference being that the base polymer and the inorganic material additive used were: 95 g of polyoxymethylene resin and 5 g of molybdic acid powder, an inorganic material additive. Other conditions were the same as in Example 36. The color change effect is shown in Table 1.
[0193] Embodiment 38
[0194] A polymer material capable of laser color change was prepared by referring to the method of Example 36, with the only difference being that the base polymer and the inorganic material additive used were: 90 g of polyformaldehyde resin and 10 g of molybdic acid powder, an inorganic material additive. Other conditions were the same as in Example 36. The color change effect is shown in Table 1.
[0195] Embodiment 39
[0196] First, 95 g of polystyrene resin and 5 g of phosphomolybdic acid powder (average particle size of 10 μm), an inorganic material additive, are fully mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 210°C to obtain a polymer material that can change color by laser.
[0197] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 210°C.
[0198] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 4 W, the laser frequency was 50 kHz, and the color change effect was shown in Table 1.
[0199] Embodiment 40
[0200] A polymer material capable of laser color change was prepared by referring to the method of Example 39, with the only difference being that the base polymer and the inorganic material additive used were: 90 g of polystyrene resin and 10 g of the inorganic material additive phosphomolybdic acid powder. Other conditions were the same as in Example 39. The color change effect is shown in Table 1.
[0201] Embodiment 41
[0202] First, 90 g of ABS resin and 10 g of inorganic material additive silicomolybdic acid powder (average particle size of 8 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 210°C to obtain a polymer material that can change color by laser.
[0203] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 210°C.
[0204] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 2 W, the laser frequency was 30 kHz, and the color change effect was shown in Table 1.
[0205] Embodiment 42
[0206] A polymer material capable of laser color change was prepared by referring to the method of Example 41, with the only difference being that the base polymer and the inorganic material additive used were: 80 g of ABS resin and 20 g of the inorganic material additive silicomolybdic acid powder. Other conditions were the same as in Example 41. The color change effect is shown in Table 1.
[0207] Embodiment 43
[0208] First, 95 g of polycarbonate resin and 5 g of ammonium molybdate powder (average particle size of 15 μm), an inorganic material additive, are fully mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 260°C to obtain a polymer material that can change color by laser.
[0209] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 270°C.
[0210] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 100 kHz, and the color change effect was shown in Table 1.
[0211] Embodiment 44
[0212] A polymer material capable of laser color change was prepared by referring to the method of Example 43, with the only difference being that the base polymer and the inorganic material additive used were: 85 g of polycarbonate resin and 15 g of ammonium molybdate powder, an inorganic material additive. Other conditions were the same as those of Example 43. The color change effect is shown in Table 1.
[0213] Embodiment 45
[0214] First, 90 g of polyethylene terephthalate resin and 10 g of inorganic material additive ammonium molybdate powder (average particle size of 12 μm) are fully mixed in a high-speed mixer for 3 minutes; then, the mixed material is placed in a twin-screw extruder for melt extrude and granulation at an extrusion temperature of 240°C to obtain a polymer material that can change color by laser.
[0215] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 250°C.
[0216] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3.5 W, the laser frequency was 45 kHz, and the color change effect was shown in Table 1.
[0217] Embodiment 46
[0218] A polymer material capable of laser color change was prepared by referring to the method of Example 45, with the only difference being that the base polymer and the inorganic material additive used were: 75 g of polyethylene terephthalate resin and 25 g of ammonium molybdate powder, an inorganic material additive. Other conditions were the same as in Example 45. The color change effect is shown in Table 1.
[0219] Embodiment 47
[0220] First, 90 g of polybutylene terephthalate resin and 10 g of sodium molybdate powder (average particle size of 7 μm), an inorganic material additive, were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 265°C to obtain a polymer material that can change color by laser.
[0221] Then, the prepared laser color-changing polymer material is injection molded into a standard sample by an injection molding machine at an injection molding temperature of 270°C.
[0222] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 2 W, the laser frequency was 30 kHz, and the color change effect was shown in Table 1.
[0223] Embodiment 48
[0224] A polymer material capable of laser color change was prepared by referring to the method of Example 47, with the only difference being that the base polymer and the inorganic material additive used were: 70 g of polybutylene terephthalate resin and 30 g of the inorganic material additive sodium molybdate powder. Other conditions were the same as in Example 47. The color change effect is shown in Table 1.
[0225] Comparative Example 1
[0226] The laser color-changing polymer material was prepared by referring to the method of Example 9, except that the base polymer and the inorganic material additives used were: 99.5 g of polymethyl methacrylate resin and 0.5 g of WO3 powder.
[0227] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 80 kHz, and the color change effect was shown in Table 1.
[0228] Comparative Example 2
[0229] The laser color-changing polymer material was prepared by referring to the method of Example 9, except that the base polymer and the inorganic material additives used were: 99.9 g of polymethyl methacrylate resin and 0.1 g of WO3 powder.
[0230] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 80 kHz, and the color change effect was shown in Table 1.
[0231] Comparative Example 3
[0232] A polymer material capable of laser color change was prepared by referring to the method of Example 26, except that the base polymer and inorganic material additives used were: 99.5 g of polyurethane resin and 0.5 g of MoO3 powder.
[0233] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 60 kHz, and the color change effect was shown in Table 1.
[0234] Comparative Example 4
[0235] A polymer material capable of laser color change was prepared by referring to the method of Example 26, except that the base polymer and inorganic material additives used were: 99.9 g of polyurethane resin and 0.1 g of MoO3 powder.
[0236] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 60 kHz, and the color change effect was shown in Table 1.
[0237] Comparative Example 5
[0238] A polymer material capable of laser color change was prepared by referring to the method of Example 36, except that the base polymer and inorganic material additives used were: 99.5 g of polyoxymethylene resin and 0.5 g of molybdic acid powder.
[0239] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3.5 W, the laser frequency was 70 kHz, and the color change effect was shown in Table 1.
[0240] Comparative Example 6
[0241] A polymer material capable of laser color change was prepared by referring to the method of Example 36, except that the base polymer and inorganic material additives used were: 99.9 g of polyoxymethylene resin and 0.1 g of molybdic acid powder.
[0242] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3.5 W, the laser frequency was 70 kHz, and the color change effect was shown in Table 1.
[0243] Comparative Example 7
[0244] A polymer material capable of laser color change was prepared by referring to the method of Example 9, except that no inorganic material additive was added, and the base polymer used was: 100 g of polymethyl methacrylate resin.
[0245] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 50 kHz, and the color change effect was shown in Table 1.
[0246] Comparative Example 8
[0247] A polymer material capable of laser color change was prepared by referring to the method of Example 1, except that no inorganic material additive was added, and the base polymer used was: 100 g of polyethylene resin.
[0248] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 4 W, the laser frequency was 60 kHz, and the color change effect was shown in Table 1.
[0249] Comparative Example 9
[0250] A polymer material capable of laser color change was prepared by referring to the method of Example 4, except that no inorganic material additive was added, and the base polymer used was: 100 g of polypropylene resin.
[0251] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3.5 W, the laser frequency was 50 kHz, and the color change effect was shown in Table 1.
[0252] Comparative Example 10
[0253] A polymer material capable of laser color change was prepared by referring to the method of Example 5, except that no inorganic material additive was added, and the base polymer used was: 100 g of polystyrene resin.
[0254] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 2.5 W, the laser frequency was 40 kHz, and the color change effect was shown in Table 1.
[0255] Comparative Example 11
[0256] A polymer material capable of laser color change was prepared by referring to the method of Example 7, except that no inorganic material additive was added, and the base polymer used was: 100 g of ABS resin.
[0257] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 2 W, the laser frequency was 20 kHz, and the color change effect was shown in Table 1.
[0258] Comparative Example 12
[0259] A polymer material capable of laser color change was prepared by referring to the method of Example 12, except that no inorganic material additive was added, and the base polymer used was: 100 g of nylon 66 resin.
[0260] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 60 kHz, and the color change effect was shown in Table 1.
[0261] Comparative Example 13
[0262] A polymer material capable of laser color change was prepared by referring to the method of Example 14, except that no inorganic material additive was added, and the base polymer used was: 100 g of polycarbonate resin.
[0263] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 80 kHz, and the color change effect was shown in Table 1.
[0264] Comparative Example 14
[0265] A polymer material capable of laser color change was prepared by referring to the method of Example 16, except that no inorganic material additive was added, and the base polymer used was: 100 g of polyoxymethylene resin.
[0266] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 4 W, the laser frequency was 80 kHz, and the color change effect was shown in Table 1.
[0267] Comparative Example 15
[0268] A polymer material capable of laser color change was prepared by referring to the method of Example 18, except that no inorganic material additive was added, and the base polymer used was: 100 g of polyurethane resin.
[0269] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 4.5 W, the laser frequency was 90 kHz, and the color change effect was shown in Table 1.
[0270] Comparative Example 16
[0271] A polymer material capable of laser color change was prepared by referring to the method of Example 20, except that no inorganic material additive was added, and the base polymer used was: 100 g of polyester elastomer resin.
[0272] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3.5 W, the laser frequency was 70 kHz, and the color change effect was shown in Table 1.
[0273] Comparative Example 17
[0274] A polymer material capable of laser color change was prepared by referring to the method of Example 22, except that no inorganic material additive was added, and the base polymer used was: 100 g of polyethylene terephthalate resin.
[0275] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 4 W, the laser frequency was 80 kHz, and the color change effect was shown in Table 1.
[0276] Comparative Example 18
[0277] A polymer material capable of laser color change was prepared by referring to the method of Example 24, except that no inorganic material additive was added, and the base polymer used was: 100 g of polybutylene terephthalate resin.
[0278] The manufactured standard sample was marked under the following conditions: the laser marking equipment was a pulse fiber laser marking machine, the laser wavelength was 355 nm, the marking speed was 1000 mm / s, the laser energy was 3 W, the laser frequency was 60 kHz, and the color change effect was shown in Table 1.
[0279] The evaluation of laser color change effect is as follows:
[0280] Laser color change is not possible --
[0281] Laser color change effect is poor*
[0282] Laser color change effect is average**
[0283] Laser color change effect is good***
[0284] Laser color change effect is very good****
[0285] Laser color change effect is very good*****
[0286] In the laser color change effect evaluation level, the more “*” there are, the better the laser color change effect is.
[0287] The laser color change effects of the above-mentioned Examples 1 to 48 and Comparative Examples 1 to 18 are shown in Table 1.
[0288] Table 1. Laser color change effect
[0289]
[0290]
[0291]
[0292]
[0293]
[0294] The above results show that the polymer without adding the specific inorganic material of the present invention (tungsten- or molybdenum-containing inorganic material) cannot achieve the color change effect (Comparative Examples 7-18); after adding the specific inorganic material of the present invention to the polymer, the polymer can have a very excellent color change effect, and achieve very excellent laser color marking on the polymer; at the same time, it can be seen from Comparative Examples 1-6 that the polymer has a good color change effect only when the addition amount of the inorganic material reaches 1% or more. Among them, Examples 16-23 and Examples 34-40 have the best laser color change effect.
[0295] In summary, the present invention provides a color-changeable polymer material prepared based on inorganic materials. The present invention prepares a color-changeable polymer material by adding a specific inorganic material as an additive to a polymer. Under the action of a laser, the polymer material has an excellent color-change effect. Laser marking is performed on the polymer material to form various color marks on the polymer material, and the obtained color marks are clear, flat and have a high contrast. At the same time, the polymer material is light in color, and color marking can be achieved on a light-colored substrate, which expands the application range of laser color marking. In addition, the preparation method of the color-changeable polymer material of the present invention is simple, easy to operate, safe, environmentally friendly, and very suitable for industrial applications. The present invention broadens the application field of polymer laser color change and has good application prospects.
Claims
1. Use of a polymer color-changing composition in preparing a laser color mark; the laser color mark is obtained by irradiating the polymer color-changing composition with a laser to produce a color pattern or text, the wavelength of the laser being 355 nm; the polymer color-changing composition is composed of the following components in weight percentage: Inorganic materials 0.1%~30%, polymers 70%~99.9%; The inorganic material is an inorganic compound containing tungsten and / or molybdenum. The tungsten-containing inorganic compound is selected from at least one of ammonium tungstate, ammonium metatungstate, ammonium paratungstate, sodium tungstate, WO3, molybdenum-doped tungsten oxide, sodium-doped tungsten oxide, titanium-doped tungsten oxide, zinc tungstate, tungstic acid, and bismuth tungstate. The molybdenum-containing inorganic compound is selected from at least one of MoO3, molybdenum aluminum oxide, molybdenum zinc oxide, molybdenum titanium oxide, molybdenum hydroxide, molybdic acid, phosphomolybdic acid, silicomolybdic acid, ammonium molybdate, ammonium metamolybdate, and sodium molybdate.
2. The use according to claim 1, characterized in that: The polymer color-changing composition is composed of the following components in weight percentage: 2% to 30% inorganic material and 70% to 98% polymer.
3. The use according to claim 1 or 2, characterized in that: The average particle size of the inorganic material is less than or equal to 100 μm.
4. The use according to claim 3, characterized in that: The average particle size of the inorganic material is 0.005 μm to 50 μm.
5. The use according to claim 4, characterized in that: The average particle size of the inorganic material is 0.01 μm to 20 μm.
6. The use according to claim 1 or 2, characterized in that: The polymer is selected from any one or more of polyethylene, polypropylene, nylon, polycarbonate, polymethyl methacrylate, polyethyl methacrylate, polybutyl methacrylate, polyoxymethylene, polyethylene terephthalate, polybutylene terephthalate, ethylene-octene copolymer, ethylene-butene copolymer, ethylene-acrylic acid copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene copolymer, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polyurethane elastomer, polyester elastomer, styrene thermoplastic elastomer, styrene-butadiene copolymer, styrene-methacrylate copolymer, polyisobutylene, ethylene-vinyl acetate copolymer, polysulfone, polyimide, cellulose acetate, unsaturated polyester, silicone resin, epoxy resin, phenolic resin, melamine resin, natural rubber, butadiene rubber, styrene-butadiene rubber, silicone rubber, fluororubber, nitrile rubber, butyl rubber, and EPDM rubber.
7. The use according to claim 6, characterized in that: The polymer is selected from polymethyl methacrylate, polyethylene, polypropylene, polystyrene, acrylonitrile-butadiene-styrene copolymer, nylon 66, polycarbonate, polyoxymethylene, polyurethane elastomer, polyester elastomer, polyethylene terephthalate, and polybutylene terephthalate.
8. The use according to claim 1 or 2, characterized in that: The preparation method of the polymer color-changing composition comprises the following steps: a. Take an inorganic material and a polymer, mix them evenly, and obtain a mixture; b. Melt-blend the mixture obtained in step a, and granulate to obtain the product.
9. A laser color marking, characterized in that: The invention is prepared by irradiating the polymer color-changing composition described in any one of claims 1 to 8 with laser to generate color patterns or words; the wavelength of the laser is 355nm.
10. The laser color marking according to claim 9, characterized in that: The laser is emitted by a Nd:YAG laser, a Nd:YVO4 laser, a fiber laser, a diode array laser or a diode laser.
11. The laser color marking according to claim 10, characterized in that: The laser is emitted by a pulsed Nd:YAG laser or a pulsed fiber laser.
12. The laser color marking according to claim 11, characterized in that: The laser energy is 0.5-8W; and / or the laser frequency is 10-100kHz; and / or the laser marking speed is 400-4000mm / s.
Citation Information
Patent Citations
Impact-resistant abs resin composition for white laser marking and its preparation and application
CN104804360B
Application of graphene as additive in preparation of laser-markable polymer material
CN105504517A
Composition capable of laser color marking and preparation method thereof
CN106566068A
Plastic paper capable of laser color marking
CN109486128A
Particles comprising marking additives for selective laser sintering-based additive manufacturing systems
CN113004692A
Cited By
Inorganic-organic composite polymer material capable of realizing laser color change as well as preparation method and application of inorganic-organic composite polymer material
CN120944221A
Colorful color change composition containing core-shell structure as well as preparation method and application of colored color change composition
CN121203264A
